Therapeutic Potential and Pharmaceutical Development of Thymoquinone: A Multitargeted Molecule of Natural Origin - Goyal, Sameer N.; Prajapati, Chaitali P.; Gore, Prashant R.; Patil, Chandragouda R.; Mahajan, Umesh B.; Sharma, Charu; Talla, Sandhya P.; Ojha, Shreesh K. (Frontiers in Pharmacology, 2017)
Thymoquinone (2-methyl-5-isopropyl-1, 4-benzoquinone-TQ) is chemically a monoterpene extracted from Nigella sativa L. seed oil (Ranunculaceae) commonly known as black cumin seed. The rigorous studies have revealed that thymoquinone the major active constituent of Nigella sativa oil brings to bear majority of pharmacological actions such as anti-inflammatory, anti-oxidant, anti-diabetic and organ-protective activities. Thymoquinone is a potent phytochemical with confirmed in-vitro efficacy used for several treatment purposes. The vast studies have revealed diverse molecular pathways of nearly all major diseases. Belonging to a phytochemical group, TQ is observed as strong lipophilic constituent hence insolubility in aqueous fluids hamper its systemic bioavailability. Hence, the physiochemical parameters and the associated toxicities are the barrier for the researchers using TQ clinically. Further studies revealed that TQ is highly light and heat sensitive, which obstruct the successful formulation for the delivery of drug. The present review aims to provide insights regarding the characteristics, pharmacokinetics and targets associated with the use of TQ in different pharmacological actions. It also suggests methods to improve the use of TQ by overcoming the associated physiochemical obstacles and the related toxicities and best utilisation for animal as well as clinical studies. According to the published reports of TQ, we suggest in-depth studies regarding the bioavailability and toxicity studies in animals as well as in humans.